A 'Classic' Challenge in Classical Mechanics

In free space , an assembly of two identical particles—each of mass m m connected by two identical uniform ropes—is rotating with constant angular velocity ω \omega about the axis passing through the center of the line segment joining them. Since the ropes have masses, they fan out and assume a curved shape, as shown in the figure.

If the distance between the midpoints of the rope is d d , tension at the midpoint of a rope is T , T, and the included angle between the ropes at the particles is θ , \theta, find the distance L L (in meters) between the particles.

Report your final answer as L 4 . L^{4}.

Assumptions:

  • m = 1 kg m =\SI{1}{\kilo\gram}
  • ω = 1 rad / s \omega=\SI[per-mode=symbol]{1}{\radian\per\second}
  • T = 1 N T = \SI{1}{\newton}
  • d = 1 m d = \SI{1}{\meter}
  • θ = 6 0 \theta = 60^\circ


The answer is 48.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Mar 26, 2018

If the shape of one of the ropes is given by the vector r = r ( s ) \mathbf{r} = \mathbf{r}(s) , where the origin is the centre of rotation, and where s s is the arc-length of the curve, then the equation for the shape of the rope is d d s [ T t ] + ρ ω 2 r = 0 \frac{d}{ds}\big[T\mathbf{t}\big] + \rho\omega^2\mathbf{r} \; = \; \mathbf{0} where ρ \rho is the linear density of the rope (assumed constant), T = T ( s ) T = T(s) is the tension in the rope and t = d r d s \mathbf{t} = \frac{d\mathbf{r}}{ds} is the unit tangent of the curve. Thus 0 = r d d s [ T t ] = d d s [ T r t ] \mathbf{0} \; = \; \mathbf{r} \wedge \frac{d}{ds}\big[T \mathbf{t}\big] \; = \; \frac{d}{ds}\big[T \mathbf{r} \wedge \mathbf{t} \big] and hence h = T r t \mathbf{h} =T\mathbf{r} \wedge \mathbf{t} is constant along the rope.

In the middle of the rope we have T = 1 T=1 , r = 1 2 i \mathbf{r} = \tfrac12\mathbf{i} and t = j \mathbf{t} = \mathbf{j} , and hence h = 1 2 k \mathbf{h} = \tfrac12\mathbf{k} . At the end of the rope we have T = T 1 T = T_1 , r = 1 2 L j \mathbf{r}= \tfrac12L\mathbf{j} and t = sin 1 2 θ i + cos 1 2 θ j \mathbf{t} = -\sin\tfrac12\theta\mathbf{i} + \cos\tfrac12\theta\mathbf{j} , and hence h = 1 2 L T 1 sin 1 2 θ k = 1 4 L T 1 k \mathbf{h} = \tfrac12LT_1\sin\tfrac12\theta \mathbf{k} = \tfrac14LT_1\mathbf{k} , and so we deduce that T 1 = 2 L T_1 = \tfrac{2}{L} .

Considering the circular motion of the particle at the end of the rope, we see that 2 L 3 = 2 × T 1 cos 1 2 θ = m × 1 2 L ω 2 = 1 2 L \tfrac{2}{L}\sqrt{3} \;=\; 2 \times T_1 \cos\tfrac12\theta \; = \; m \times \tfrac12L\omega^2 \;=\; \tfrac12L and hence L 4 = 48 L^4 = \boxed{48} .

Please explain how did you get the first equation

Rakshit Singhal - 11 months, 1 week ago

Log in to reply

Consider a small segment of string. The tensions in the string at each end of this small segment must provide the central acceleration needed for the segment to rotate with angular speed ω \omega . Thus ( T + δ T ) ( t + δ t ) T t = ρ δ s × r ω 2 (T+\delta T)(\mathbf{t}+\delta\mathbf{t})-T\mathbf{t} =-\rho \delta s \times \mathbf{r}\omega^2 Divide by δ s \delta s , and let δ s \delta s tend to 0 0 .

Mark Hennings - 11 months, 1 week ago

Log in to reply

Thank you very much!

Rakshit Singhal - 11 months, 1 week ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...